Orthodontic-surgical treatment of class III malocclusion with mandibular asymmetry - Bergamo,Ana Zilda Nazar (2011)
Class III skeletal malocclusion may present several etiologies, among which maxillary deficiency is the most frequent. Bone discrepancy may have an unfavorable impact on esthetics, which is frequently aggravated by the presence of accentuated facial asymmetries. This type of malocclusion is usually treated with association of Orthodontics and orthognathic surgery for correction of occlusion and facial esthetics. This report presents the treatment of a patient aged 15 years and 1 month with Class III skeletal malocclusion, having narrow maxilla, posterior open bite on the left side, anterior crossbite and unilateral posterior crossbite, accentuated negative dentoalveolar discrepancy in the maxillary arch, and maxillary and mandibular midline shift. Clinical examination also revealed maxillary hypoplasia, increased lower one third of the face, concave bone and facial profiles and facial asymmetry with mandibular deviation to the left side. The treatment was performed in three phases: presurgical orthodontic preparation, orthognathic surgery and orthodontic finishing. In reviewing the patient's final records, the major goals set at the beginning of treatment were successfully achieved, providing the patient with adequate masticatory function and pleasant facial esthetics.